Design Criteria for Minimum Passing Zone Lengths: Operational Efficiency and Safety Considerations. Issue 1 (January 2015) - Moreno, Ana Tsui; Llorca, Carlos; Lenorzer, Annique; Casas, Jordi; García, Alfredo
Passing zones are provided to improve operational efficiency of two-lane highways. Minimum passing zone lengths of 120 m were established by FHWA and AASHTO. Some studies indicate that lengths may need to be increased, but no changes have been recommended, pending further research. The objective of this study was to develop design and marking criteria for minimum passing zone lengths, with traffic operational efficiency and safety taken into consideration. First, a traffic microsimulation was conducted with AIMSUN software. The calibration and validation included the observation of 1, 750 passing maneuvers in Spain. Results indicated that passing zones shorter than 250 m added little to operational efficiency. Second, a reliability analysis was applied. The analysis quantified the probability that a passing maneuver was completed beyond the end of the passing zone (noncompliant passing maneuver). Then the number of noncompliant passing maneuvers was calculated. Traffic flow and passing zone length were contributing factors. Findings from the analysis indicated that the minimum passing zone length should be increased to a minimum of 275 m for high traffic volumes, 300 m for medium traffic volumes, and 350 m for low traffic volumes. With these lengths, noncompliant passing maneuvers decrease. The marginal increase in the minimum length of passing zones can potentially improve safety without significantly reducing operational efficiency. The results can be used by practitioners to establish minimum passing zone length on the basis of hourly volumes and level of risk.